2015
DOI: 10.1038/onc.2015.192
|View full text |Cite
|
Sign up to set email alerts
|

The biology of circulating tumor cells

Abstract: Metastasis is a biologically complex process consisting of numerous stochastic events which may tremendously differ across various cancer types. Circulating tumor cells (CTCs) are cells that are shed from primary tumors and metastatic deposits into the blood stream. CTCs bear a tremendous potential to improve our understanding of steps involved in the metastatic cascade, starting from intravasation of tumor cells into the circulation until the formation of clinically detectable metastasis. These efforts were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
381
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 447 publications
(389 citation statements)
references
References 119 publications
(151 reference statements)
4
381
0
4
Order By: Relevance
“…While their repressive activity on several epithelial genes has been shown to involve a direct binding to promoter regions, their ability to induce mesenchymal genes rather implicates indirect and often unknown mechanisms (6)(7)(8)(9). Closely linking EMT to CTC, the expression of EMT mediators has been detected in CTCs in animal models (2,10) and in subpopulations of CTCs isolated from cancer patients including breast cancer patients, where they associate with poor clinical parameters and to the particularly aggressive "triple-negative breast cancer" (TNBC) subtype (5,11,12). It has thus been suggested that CTCs expressing EMT features could represent a premetastatic population, socalled metastasis-initiating cells (MIC).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…While their repressive activity on several epithelial genes has been shown to involve a direct binding to promoter regions, their ability to induce mesenchymal genes rather implicates indirect and often unknown mechanisms (6)(7)(8)(9). Closely linking EMT to CTC, the expression of EMT mediators has been detected in CTCs in animal models (2,10) and in subpopulations of CTCs isolated from cancer patients including breast cancer patients, where they associate with poor clinical parameters and to the particularly aggressive "triple-negative breast cancer" (TNBC) subtype (5,11,12). It has thus been suggested that CTCs expressing EMT features could represent a premetastatic population, socalled metastasis-initiating cells (MIC).…”
Section: Introductionmentioning
confidence: 99%
“…EMT indeed provides epithelial tumor cells with enhanced migratory, invasive, and survival abilities that participate in the liberation of CTCs into the circulation (1,2,4,5). A variety of EMT-inducing extracellular signals and signaling pathways have been shown to converge on the expression of EMT transcription factors including the Snail and ZEB families, Twist, and E47 (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, new important insights into the biology of CTCs combined with various innovative technologies have been reported ( 31 ), and technical platforms for combined enrichment, detection, and characterization of CTCs are on the horizon.…”
Section: Ctcsmentioning
confidence: 99%
“…CTCs also have potential for use in evaluating drug resistance mechanisms and may have utility in estimation of the risk of metastatic relapse and progression. Unlike the characterization of primary tumors, which provides only a static view at the time of diagnosis, analyzing CTCs may improve understanding of the different steps involved in the metastatic cascade, from invasion of tumor cells into the bloodstream to the formation of clinically detectable metastases (7 ).…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%